Automated Conversion of Building Information Modeling (BIM) Geometry Data for Window Thermal Performance Simulation - Changmin Kim; Changyoung Park; Changho Choi; Hyangin Jang (Advances in Civil Engineering)
A window set is defined as a window where the frame and the glass are combined and is used at the part that comes into contact with the air. As the performance evaluation of window sets has gained significance, the need for software that can simulate window set performance has also increased accordingly. However, the simulation of window sets is not carried out efficiently due to the difficulty in the window set modeling. Meanwhile, the design of building information modeling has recently proliferated so that the window set BIM library is distributed online. If such a window set BIM library is utilized in the window set simulation, it is expected that the productivity issue that occurs in the simulation process could be improved. Therefore, this study proposes a method to automatically convert the information required in the simulation of the window set heat transfer coefficient from the BIM. In order to achieve the purpose of this study, the following procedure is carried out. First, the framework for converting the information required in the simulation of the window set heat transfer coefficient from the BIM is suggested. Second, the method to extract and convert BIM data based on the suggested framework is proposed. Lastly, the BIM data conversion program is developed, and its performance is validated by applying the window set BIM case. The case study result showed that the information converted and entered from the window set data BIM conversion program coincided with the information entered in the window set BIM. It is expected that the result of this study will increase the productivity of window set simulations, which will lead to the increased use of certification through these simulations.